The Evaluation of the Functional Capacity of the Cylindric Pre-Stressed Tanks - Emilia Neagu; Sergiu Călin; Ciprian Asăvoaie; Mugurel Cloşcă (Bulletin of the Polytechnic Institute of Jassy: Constructions, Architechture Section, 2010)
This paper approaches the problem of diagnosing the degradation and the safety estate in exploatation of the cylindrical tanks made out of pre-prestressed concrete, affected by execution errors, especially generated by the design non-observance stipulations, being suggested by a situation which hasn’t been signalized into the specialty literature from our country. The effectuated study aimed to evaluate the functional capacity of cylindrical tanks, being proposed an original way (methodology) of identifying the real loading level of the horizontal sections from the walls of the pre-prestressed cylindrical tanks with cables and which relies on an original grapho-analytical procedure. This way there were realized etalon-graphics for different types of tanks and their geometrical and technical characteristics which allow a soft evaluation of the nominal functioning capacity of the analysed objectives, by comparing the quantity of existing reinforcement with the need quantity.